Metabolites from the marine-derived fungi : Nigrospora sp. PSU-F11 and PSU-F12, Xylaria sp. PSU-F100 and Fusarium sp. PSU-F135 - Nanthaphong Khamthong (Prince of Songkla University, 2010)
Thesis (M.Sc., Organic Chemistry)--Prince of Songkla University, 2009